Effect of Alternanthera dentata (Moench) Stuchlík Extract Concentration on the Antioxidant Activity and Physicochemical Properties of Lip Balm - Cindi Simbolon; Neswati -Neswati; Santosa Santosa (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Alternanthera dentata (Moench) Stuchlík is a wild plant widely distributed in tropical regions. A. dentata (Moench) Stuchlík contains bioactive compounds that act as antioxidants. The addition of natural coloring to lip balm is useful for increasing its functional value; not only is it useful for moisturizing and maintaining healthy lips, but it also improves the aesthetics of the user. The aim of this study was to determine the optimal concentration of A. dentata (Moench) Stuchlík leaf extract in the formulation based on the antioxidant activity and physicochemical properties of the lip balm. The results showed that high levels of A. dentata (Moench) Stuchlík extract increased the antioxidant activity of lip balm, but molding the formulation into a stable stick form became difficult. Lip balm has very low antibacterial activity. The best addition of A. dentata (Moench) Stuchlík extract was 1.2 %. The physicochemical properties of lip balm were antioxidant activity at 82.7 %, antibacterial activity of 0.34 mm, homogeneous, melting point of 55 °C, pH 4.97, stability on the fourth day, and humidity of 47.27%. The sensory analysis of the product was carried out by panelists using a scale of 1-5 (very dislike - very like), showing product color 4.24, texture 3.63, and aroma 4.04. However, the addition of 1.2% extract resulted in a softer lip balm texture, making it less suitable for molding into a stick form. Therefore, the product is more appropriately packaged in small containers, such as pots or screw-cap jars, to maintain its practicality and ease of use. Further studies are recommended to investigate the stability of natural colorants in the formulation. Overall, A. dentata (Moench) Stuchlík extract shows strong potential as a natural coloring agent while also providing antioxidant properties that may help maintain lip health. Contribution to Sustainable Development Goals (SDGs):SDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production